2018
DOI: 10.1021/acs.jafc.8b02545
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber Increases Butyrate-Producing Bacteria and Improves the Growth Performance of Weaned Piglets

Abstract: The study investigated the impact of dietary fibers on the performance, fecal short-chain fatty acids, nutrient digestibility, and bacterial community in weaned piglets with the control group (CON) and dietary supplementation of 5% corn bran (CB), 5% wheat bran (WB), or 5% soybean hulls (SB). The piglets in CB and WB groups showed greater weight gain and feed efficiency ( p < 0.05) in comparison to piglets in CON and SB groups. Fecal samples from piglets in CB, SB, and WB groups contained greater ( p < 0.05) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
95
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 43 publications
13
95
2
1
Order By: Relevance
“…A good gut microbiota is able to benefit the host by regulating physiological process and mucosal immunity such as suppressing proliferation of enteric pathogens [20], strengthening integrity of intestinal barrier on epithelial cells [21,22] and producing antimicrobial peptides in mucus layer [23]. In this study, Bacteroides and Firmicutes were the two dominant phyla, and Prevotella was the dominant bacterial species at the genus level, corresponding with the previous studies in which the most abundant phyla detected in the fecal samples of weaned piglets were Firmicutes and Bacteroides [24][25][26][27]. This research showed that Firmicutes abundance was increased in the CPB group but decreased in the antibiotic group.…”
Section: Discussionsupporting
confidence: 85%
“…A good gut microbiota is able to benefit the host by regulating physiological process and mucosal immunity such as suppressing proliferation of enteric pathogens [20], strengthening integrity of intestinal barrier on epithelial cells [21,22] and producing antimicrobial peptides in mucus layer [23]. In this study, Bacteroides and Firmicutes were the two dominant phyla, and Prevotella was the dominant bacterial species at the genus level, corresponding with the previous studies in which the most abundant phyla detected in the fecal samples of weaned piglets were Firmicutes and Bacteroides [24][25][26][27]. This research showed that Firmicutes abundance was increased in the CPB group but decreased in the antibiotic group.…”
Section: Discussionsupporting
confidence: 85%
“…The human gut microbiota is a complex community and is important for the health status of the host . Alterations in the gut microbiota and diet have been found to be associated with the pathogenesis of several human diseases . Probiotic supplementation has been found to be associated with improvements in health and the intestinal microbial composition, and the supplementation of L. fermentum has been shown to modulate the intestinal microbiota in piglets .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Alterations in the gut microbiota and diet have been found to be associated with the pathogenesis of several human diseases. [36][37][38][39][40] Probiotic supplementation has been found to be associated with improvements in health and the intestinal microbial composition, 24,41 and the supplementation of L. fermentum has been shown to modulate the intestinal microbiota in piglets. 42 As the global composition and the presence of pathogens or beneficial bacteria are relevant to the host's health, we analyzed the composition of the test animals over 13 weeks of feeding of bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported PHB as an alternative diet additive for MCAs can supply short‐chain‐length fatty acids (SCFAs) for commensal bacteria and host cells during PHB degradation in the digestive tracts, which aids the maintenance of a balanced microbiome in the gastrointestinal tract . Similar to these reports, microbial extracellular hydrolytic enzymes in the digestive tract generate 3HB and oligo‐3HB, both of which can function as an energy source and stimulate the activity of digestive enzymes for better piglet growth performance . The growth‐promoting effect of PHB on the fish could be attributed to PHB degradation and the accompanying release of oligo‐3HB and monomeric β‐hydroxybutyric acid (3HB), which have documented positive effects on animal and human health .…”
Section: Discussionmentioning
confidence: 71%